2019
DOI: 10.5539/gjhs.v11n9p182
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Education and Residence on Current Use of Contraception in Ethiopian Women

Abstract: BACKGROUND: Maternal and infant mortality is high in Ethiopia. An underlying cause of maternal and infant mortality is unintended pregnancy, which is inversely associated with contraceptive use. Hence, the use of contraception can necessarily be increased to reduce the mortality rate of mother and infant. OBJECTIVES: This study aims to examine the effect of educational attainment and place of residence on contraceptive use among Ethiopian women of childbearing ages. METHODS: Data are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…However, this limitation does not have that much significant concern due to the coincidence of the results of the current study to many recent literatures (e.g. [4], [5], [7], [9]).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 54%
See 1 more Smart Citation
“…However, this limitation does not have that much significant concern due to the coincidence of the results of the current study to many recent literatures (e.g. [4], [5], [7], [9]).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 54%
“…Woman's educational level: Stanfors and Larsson [6] concluded that the educational level is a crucial factor of contraceptive use in Sub-Saharan Africa. Ahmed and Zahangir [7] found that women with secondary or higher education levels have significantly higher odds of contraceptive use compared to those who were illiterate, after adjusting for many confounders such as total children ever born, number of living children, desire of more children, wealth index, respondent currently working, region and religion.…”
Section: Introductionmentioning
confidence: 99%
“…Education improves cognitive skills, awareness about health, nancial resources and decision-making power. It provides improved access to the mass media, knowledge and attitude about family planning, access to contraception, correct use of contraception, and nally promotes contraceptive use (57).…”
Section: Geographical Variation and Clustering Of Modern Contraceptivmentioning
confidence: 99%
“…Education improves cognitive skills, awareness about health, nancial resources and decision-making power. It provides improved access to the mass media, knowledge and attitude about family planning, access to contraception, correct use of contraception, and nally promotes contraceptive use (58).…”
Section: Geographical Variation and Clustering Of Modern Contraceptivmentioning
confidence: 99%